Concepts in String Playing Reflections by Artist-Teachers at the Indiana University School of Music - Grodner, Murray (Indiana University Press, 1979)
Indiana University's School of Music is widely recognized as one of the world's outstanding performance-oriented teaching institutions. One of the strongest departmenfs in a consistently excellent school is the string faculty. Especially for this vol-ume, twelve artist-teachers from the string department have contributed essays on aspects of their art relevant to practicing, performing, or pedagogy. Although the authors have varied backgrounds-as soloists, chamber music players, orchestra members-and differ widely in age and birthplace, several themes recur throughout the volume: how to make the most of limited practice time, the importance of economy of effort, the similarities of playing a musical instrument and athletic endeavors, and, above all, the respect for a composer's intent that must be every musician's goal. The contributors are James Buswell IV (violin), Josef Gingold (violin), Murray Grodner (bass), Franco Gulli (violin), Georges Janzer (viola), Albert Lazan (violin), Fritz Magg (cello), Laurence Shapiro (violin), Abraham Skernick (viola), Janos Starker (cello), Helga Ulsamer Winold (cello), and Tadeusz Wroński (violin).